Examination of asynchronous volumetric and frequency communication patterns in online courses and their impact on adult learner satisfaction - (:unkn) unknown (My University, 2006)
The purpose of this study was to investigate the relationship of online discussion board interactions of adult learners and their satisfaction with their experience. Specifically, this study's objectives were to examine the asynchronous volumetric and frequency textual communication patterns through online discussion boards and the association to adult learner satisfaction for 102 electronically surveyed adult learners at a mid-western university during the 2005-2006 academic year. Highly reliable (Cronbach alpha = 0.97) and valid data were collected from a learner satisfaction form developed specifically for the outcome variable o f this study. Exploratory factor analysis provided evidence that the data collected from the form were asymmetrically sub-structured into four distinct factors. Communication constructs of momentum, force, and energy were created from physical parameters and determined to be the main predictor variables in this study. The communication constructs were significantly related to the outcome of learner satisfaction and collectively constituted the structural core of this study’s model as determined by correlations and linear regression modeling. Moderator variables of learner prior experience and learner prior satisfaction were found to create a highprecision model of asynchronous volumetric and frequency communication patterns and learner satisfaction through correlations and interaction effects in regression analysis. The study provides core and high-precision models that link asynchronous textual communication for discussion boards in online courses to adult learner satisfaction.
Keywords: Electronic discussion groups; Distance education; Online social networks; Distance education students; Adult students; Communication in education